The Impact of Diffusion on the Adoption of an Olive Oil Extraction Technique with a Continuous Two-Phase System without Pollution: Case of Study in Two Mediterranean Regions, Bouira in Algeria and Cordoba in Spain - Labdaoui, Djamel; Hadj Smaha, Djillali; Larid, Mohammed; Gomez, A.C. (Journal of Applied Environmental and Biological Sciences, 2016)
In the Mediterranean Basin, the olive growing sector has a great effect on the rural economy, the regional heritage, and the environment. Based on an investigation conducted respectively on a sample of two olive oil growing areas (Bouira in Algeria and Cordoba in Spain), a comparative study has been the subject of a diagnosis of the state of the olive oil factories, their functioning mode, their impact on the quality of oil, the recovery of waste (pomace and margins) that they produce on the environment, as well as the prospects of adoption of a two-phase extraction system which is considered as ecological. The results have shown that in the region of Cordoba, the adoption of this model by olive oil factories since the 1990s has witnessed unprecedented progressive evolution which has a tendency to generalize. Although this system is within the scope of technologies called "clean ", and because of the lack of popularization and consciousness-raising, it is still unknown in the zone of Bouira in Algeria. The research has also shown that we should move towards the use of innovatory and more appropriate techniques to allow the production of quality oil, water and energy saving, reduction of pollution from the source, and have to be increasingly used by the factories concerned with environmental issues, and desirous of keeping their share in the market. Therefore, it is necessary for the competent authorities to become conscious of the sustainable development of the sector
Keywords: Olive-oil factories; pollution; margins; two-phase system; adoption and diffusion